Full-body kinematics and vertical ground reaction forces in elite ten-pin bowling: a field study - Seiferheld, B. E.; Frost, J.; Østergaard, T. B.; Krog, M. S.; Klitgaard, K. K.; de Zee, M. (Sensors, 2023)
The purpose was to investigate full-body kinematics and vertical ground reaction forces in the lower extremities of the delivery and to determine delivery changes over time after many deliveries in ten-pin bowling. Six male elite ten-pin bowlers completed six bouts of twelve bowling deliveries, all strike attempts, while measuring full-body kinematics and vertical ground reaction forces. Full-body joint angles, peak vertical ground reaction forces in the feet, vertical breaking impulse, centre of mass velocity, bowling score, and ball release velocity (BRvel) were measured. Results revealed that the BRvel was significantly decreased over bouts (p < 0.001). Additionally, increased flexion of the dominant wrist (p < 0.001) and elbow (p = 0.004) prior to ball release (BR) and increased pronation of the dominant wrist during BR (p = 0.034) were observed at later bouts. It was concluded that these kinematic changes in the dominant wrist and elbow prior to and during BR were performed to compensate for the change in traction between ball and lane during a bowling match. This, in turn, caused a decrease in BRvel. A conservation of energy perspective was discussed to highlight training applications and possibilities to enhance elite athletes` bowling performance.